Multiwavelength Campaign Observations of a Young Solar-type Star, EK Draconis. II. Understanding Prominence Eruption through Data-driven Modeling and Observed Magnetic Environment - Kosuke Namekata; Kai Ikuta; Pascal Petit; Vladimir S. Airapetian; Aline A. Vidotto; Petr Heinzel; Jiří Wollmann; Hiroyuki Maehara; Yuta Notsu; Shun Inoue; Stephen Marsden; Julien Morin; et al. (The Astrophysical Journal, 2024)
EK Draconis, a nearby young solar-type star (G1.5V, 50–120 Myr), is known as one of the best proxies for inferring the environmental conditions of the young Sun. The star frequently produces superflares, and Paper I presented the first evidence of an associated gigantic prominence eruption observed as a blueshifted H α Balmer line emission. In this paper, we present the results of the dynamical modeling of the stellar eruption and examine its relationship to the surface starspots and large-scale magnetic fields observed concurrently with the event. By performing a 1D freefall dynamical model and a 1D hydrodynamic simulation of the flow along the expanding magnetic loop, we found that the prominence eruption likely occurred near the stellar limb (12 ${}_{-5}^{+5}$ -16 ${}_{-7}^{+7}$ degrees from the limb) and was ejected at an angle of ${15}_{-5}^{+6}$ -24 ${}_{-6}^{+6}$ degrees relative to the line of sight, and the magnetic structures can expand into a coronal mass ejection. The observed prominence displayed a terminal velocity of ∼0 km s ^−1 prior to disappearance, complicating the interpretation of its dynamics in Paper I. The models in this paper suggest that prominence’s H α intensity diminishes at around or before its expected maximum height, explaining the puzzling time evolution in observations. The Transiting Exoplanet Survey Satellite light curve modeling and (Zeeman) Doppler Imaging revealed large midlatitude spots with polarity inversion lines and one polar spot with dominant single polarity, all near the stellar limb during the eruption. This suggests that midlatitude spots could be the source of the gigantic prominence we reported in Paper I. These results provide valuable insights into the dynamic processes that likely influenced the environments of early Earth, Mars, Venus, and young exoplanets.